Long-term impact of systemic bacterial infection on the cerebral vasculature and microglia - Püntener, Ursula (BioMed Central, 2012)
BACKGROUND: Systemic infection leads to generation of inflammatory mediators that result in metabolic and behavioural changes. Repeated or chronic systemic inflammation leads to a state of innate immune tolerance: a protective mechanism against overactivity of the immune system. In this study, we investigated the immune adaptation of microglia and brain vascular endothelial cells in response to systemic inflammation or bacterial infection. METHODS: Mice were given repeated doses of lipopolysaccharide (LPS) or a single injection of live Salmonella typhimurium. Inflammatory cytokines were measured in serum, spleen and brain, and microglial phenotype studied by immunohistochemistry. To assess priming of the innate immune response in the brain, mice were infected with Salmonella typhimurium and subsequently challenged with a focal unilateral intracerebral injection of LPS. RESULTS: Repeated systemic LPS challenges resulted in increased brain IL-1β, TNF-α and IL-12 levels, despite attenuated systemic cytokine production. Each LPS challenge induced significant changes in burrowing behaviour. In contrast, brain IL-1β and IL-12 levels in Salmonella typhimurium-infected mice increased over three weeks, with high interferon-γ levels in the circulation. Behavioural changes were only observed during the acute phase of the infection. Microglia and cerebral vasculature display an activated phenotype, and focal intracerebral injection of LPS four weeks after infection results in an exaggerated local inflammatory response when compared to non-infected mice. CONCLUSIONS: These studies reveal that the innate immune cells in the brain do not become tolerant to systemic infection, but are primed instead. This may lead to prolonged and damaging cytokine production that may have a profound effect on the onset and/or progression of pre-existing neurodegenerative disease.